Understanding the Male Homosexual Experience Grades 11, 12 - Nagorski, Alec P. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1977)
This unit has been designed as a means of sensitizing class members to various forms of social discrimination that exist against homosexuals. Each lesson can be adapted to a fifty minute class period; the steps indicate transitions in topic development, the key questions are recommended as guidelines for facilitating class discussion. Students will be confronted with suppositions, which are thought to assimilate their life experiences, and simultaneously reflect homosexual oppression. This will enable them to: (1) become familiar with homosexuals as ordinary human beings with a sexual preference for same sex members, and (2) attain greater empathy and understanding of the homosexual's dilemma. By representing the homosexual's experience in having their sexual identity oppressed, students will learn to understand: (1) why homosexuals may often hide their sexual orientation and/or behavior, and (2) the struggle that frequently occurs in affirming one's homosexuality. Through these lessons, students begin to realize the value of non-heterosexist and supportive individuals for homosexuals in adjusting to their homosexuality. Successful completion of this unit may be evaluated, by requiring students to design and conduct their own research, in finding possible explanations to why homosexuals are discriminated against in the American culture. (Author)
ERIC Note: Pages 9-12 and 20-24 of original document are copyrighted and therefore not included.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adolescents; Attachment Behavior; Behavior Change; Curriculum Guides; Emotional Development; Homosexuality; Interpersonal Relationship; Males; Program Descriptions; Sensitivity Training; Sex Stereotypes; Social Discrimination; Reports, Descriptive